2020
DOI: 10.3390/ijerph17113833
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence Trends in the Oil Shale Industrial Region in Estonia

Abstract: Large oil shale resources are found in Eastern Estonia, where the mineral resource is mined, excavated, and used for electricity generation and shale oil extraction. During industrial activities in the last 100 years, pollutants have been emitted in large amounts, some of which are toxic and carcinogenic. The current study aims to analyse time trends in cancer incidence in the oil shale industry-affected areas and compare them with overall cancer incidence rates and trends in Estonia. We analysed Estonian Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Twelve studies showed that exposure to air pollution was associated with increased risk for kidney-related outcomes. Three studies reported that exposed populations had a lower risk of kidney cancer [ 31 , 36 , 37 ]. One study reported no significant difference in the risk for hypertension or diabetes between exposed and unexposed populations [ 33 ], while the remaining nine studies reported mixed findings.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies showed that exposure to air pollution was associated with increased risk for kidney-related outcomes. Three studies reported that exposed populations had a lower risk of kidney cancer [ 31 , 36 , 37 ]. One study reported no significant difference in the risk for hypertension or diabetes between exposed and unexposed populations [ 33 ], while the remaining nine studies reported mixed findings.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, children living in the area have a higher risk of developing asthma (5,6). Also a recent study has found the lung cancer age-standardized incidence rate being higher in Ida-Viru County compared to Estonia overall (7). One of the weaknesses in epidemiological studies has been poor exposure data, as discussed by Orru et al (4,6).…”
Section: Introductionmentioning
confidence: 98%
“…Previous reports have shown that exposure to VCM causes liver damage, liver enlargement, hepatocyte necrosis, and cirrhosis in humans. Moreover, an impact of VCM was found on different kinds of liver cancer, such as primary hemangiosarcoma and hepatic vascular endothelial cell tumors (12,13).…”
Section: Introductionmentioning
confidence: 99%